Human Rights in Orthodoxy and Islam A Comparative Approach - Boldişor, Adrian ca. 20./21. Jh. (Review of ecumenical studies, 2015)
In a world where increasingly more voices from different geographical areas talk speak about equality between people, religions are called to uphold and preach human dignity and rights of all people, without taking account of race, sex or religion. In the interreligious dialog, the meetings between representatives of Christianity and Islam have multiplied considerably and they deal with themes analyzing preaching and defending human rights at all levels of life. From the preceding discussion it is clear that the human rights issue is quite sensitive, especially after the latest political, economic and social events that have shaken the world in which we live. After the period of time that the proclamation and recognition of global human rights were made as contained in the various international documents, it was passed into a new phase where the followers of different religions should work together for human dignity and human rights.